Gambaran Lama Hari Rawat Inap Pasien Covid-19 Berdasarkan Karakteristik Demografi, Klinis dan Hasil Laboratorium Pasien di Ruang Perawatan Covid-19 RSUD H. Boejasin Pelaihari Tahun 2021 - Theresia Jamini (Jurnal Penelitian UPR, 2021)
Corona virus (SARS-CoV-2) is a severe acute respiratory syndrome that moves quickly from human to human through direct contact which spreads so fast every day that the number of infected people continues to increase. Increased impact on length of stay, which is an indicator to determine hospital care, quality control, use of hospital services that can be assessed from various aspects. Find out the description the length of stay of covid-19 patients based on demographic, clinical and laboratory characteristics of patients in the medical ward of covid-19 H. Boejasin Pelaihari Hospital. This type of research is observational with retrospective descriptive design using with total sampling method. The number of samples is 208 medical record date of patients. Instruments for data collection of documentation sheets. Data analysis using frequency distribution table.The results showed that the number of days hospitalized for Covid-19 patients from all dominant characteristics was 14 days, the most cases were in the elderly 97 respondents (46.6%), gender of male 110 respondents (52.9%), had commorbid 125 respondents (60.1%), did not have fever when they entered the hospital, 130 respondents (62.5%), and low lymphocyte values 99 respondents (47.65%). The length of days of hospitalization for Covid-19 patients from all dominant characteristics is 14 days. More than patients whose length of stay is > 14 days.